Unveiling the pinning behavior of charged domain walls in BiFeO3 thin films via vacancy defects. (March 2020) - Geng, W.R.; Tian, X.H.; Jiang, Y.X.; Zhu, Y.L.; Tang, Y.L.; Wang, Y.J.; Zou, M.J.; Feng, Y.P.; Wu, B.; Hu, W.T.; Ma, X.L.
Abstract: Manipulation of electronic states in functional ferroelectrics is promising for next generation electronics devices. The charged domain walls in ferroelectric materials especially facilitate the electronic state modulation and are promising for developing interface-based devices. However, the major challenges impeding the application are their intentional manipulation and the elusive pinning behavior. Here, results that charged domain walls in BiFeO3 films can be pinned and regulated by oxygen vacancy planar distributions controlled by oxygen pressure during film growth are reported. Using aberration-corrected scanning transmission electron microscopy complemented by theoretical simulations, rich pinning behavior of tail-to-tail charged domain walls by oxygen vacancy plates is revealed. At high annealing oxygen pressure, 71° charged domain walls are stabilized by narrow vacancy plates. Decreasing the oxygen pressure, the transformation from 71° to 109° charged domain walls happens by expanding the vacancy plates, as collaborated by phase field simulations. Besides, the 71°-109° charged domain wall pairs are stabilized due to further interaction between two neighboring vacancy plates. These results provide the active modulation of the electronic states and illuminate the rich pinning behavior of domain walls by vacancy defects in ferroelectrics, which in turn could provide implications for designing potential electronics devices. Graphical Abstract: Image, graphical abstract